PENDIDIKAN KARAKTER BERBASIS STILISTIKA BAHASA (ANALAISIS SEMANTIK AYAT-AYAT PENDIDIKAN) - Yunaldi Yunaldi (FORUM PAEDAGOGIK, 2021)
Language is a medium or a tool to convey feelings or what is felt and thought by humans, in this case the author thinks the importance of language wealth in terms of style in the delivery and expression of ideas to be able to be understood properly, studies and discussions in this paper are intended to describe some language styles expressed in educational verses and how to understand and apply the meaning expressed by those verses in education, in order to be able to transform the values that will be character for students. Assuming that language in transforming values, knowledge and characters has very important role and deemed necessary to be studied more deeply. The analysis used in this study is a thematic analysis of the verses of education with the focus of study how the forms of exposure to educational verses and their meaning and their application in character education. The findings of this study there areÂ  some patterns of language style presentations contained in educational verses include story style, parables, speech, innuendo, dialogue, and wisdom. The conclusion of this study is that there are types of language styles that can be implicated in educationÂ Bahasa merupakan media atau alat untuk menyampaikan perasaan atau apa yang dirasakan dan dipikirkan oleh manusia, dalam hal ini penulis menganggap pentingnya kekayaan bahasa ditinjau dari uslub atau style dalam penyampaian dan pengungkapan ide agar dapat dipahami dengan baik, kajian ini dimaksudkan untuk mendeskripsikan beberapa gaya bahasa yang diungkapkan dalam ayat-ayat pendidikan dan bagaimana memahami dan menerapkan makna yang diungkapkan oleh ayat-ayat tersebut dalam pendidikan, agar mampu mentransformasikan nilai-nilai yang akan menjadi karakter siswa. Analisis yang digunakan dalam penelitian ini adalah analisis tematik ayat-ayat pendidikan dengan fokus kajian bagaimana bentuk pemaparan ayat-ayat pendidikan dan maknanya serta penerapannya dalam pendidikan karakter. Temuan penelitian ini terdapat beberapa pola penyajian gaya bahasa yang terdapat dalam ayat-ayat pendidikan meliputi gaya cerita, perumpamaan, tuturan, sindiran, dialog, dan hikmah. Kesimpulan penelitian ini adalah terdapat beberapa pilihan gaya bahasa yang bisa diimplikasikan dalam pendidikan